Systematic Risk Management and Profitability: A Case Study of Selected Financial Institutions in Sri Lanka - Nimalathasan, B.; Pratheepkanth, P. (My University, 2012)
The main objective of the study is to identify the impact of Systematic risk management on Profitability, during 2007 to 2011 (05 years). In the present study, Systematic Risk Management [i.e., Degree of Financial leverage (DFL) and Degree of Operating leverage (DOL) as independent variable and Profitability (i.e., Net Profit, Return on Capital Employed (ROCE) and Return on Equity (ROE)] as the dependent variable are considered. In order to select the sample, convenience sampling techniques method is used. The study suitably used both secondary data. Operational hypotheses are formulated, results revealed that systematic risk management has a positive association(r= 0.755, p is less then 0.05) with Profitability. Further, Systematic risk management is enhanced by DFL and DOL in the selected financial institutions where the beneficial impacts are observed on profitability. Therefore, they have to pay more attention for tuning systematic risk management techniques. This study would hopefully benefit the academicians, researchers, policy-makers and practitioners of Sri Lanka and other similar countries through exploring the impact of systematic risk management on profitability, and pursuing policy to improve the current status of it.